Organic micropollutant removal in full-scale rapid sand filters used for drinking water treatment in The Netherlands and Belgium. (December 2020) - Di Marcantonio, Camilla; Bertelkamp, Cheryl; van Bel, Nikki; Pronk, Tessa E.; Timmers, Peer H.A.; van der Wielen, Paul; Brunner, Andrea M.
Abstract: Biological treatment processes have the potential to remove organic micropollutants (OMPs) during water treatment. The OMP removal capacity of conventional drinking water treatment processes such as rapid sand filters (RSFs), however, has not been studied in detail. We investigated OMP removal and transformation product (TP) formation in seven full-scale RSFs all treating surface water, using high-resolution mass spectrometry based quantitative suspect and non-target screening (NTS). Additionally, we studied the microbial communities with 16S rRNA gene amplicon sequencing (NGS) in both influent and effluent waters as well as the filter medium, and integrated these data to comprehensively assess the processes that affect OMP removal. In the RSF influent, 9 to 30 of the 127 target OMPs were detected. The removal efficiencies ranged from 0 to 93%. A data-driven workflow was established to monitor TPs, based on the combination of NTS feature intensity profiles between influent and effluent samples and the prediction of biotic TPs. The workflow identified 10 TPs, including molecular structure. Microbial community composition analysis showed similar community composition in the influent and effluent of most RSFs, but different from the filter medium, implying that specific microorganisms proliferate in the RSFs. Some of these are able to perform typical processes in water treatment such as nitrification and iron oxidation. However, there was no clear relationship between OMP removal efficiency and microbial community composition. The innovative combination of quantitative analyses, NTS and NGS allowed to characterize real scale biological water treatments, emphasizing the potential of bio-stimulation applications in drinking water treatment. Graphical abstract: Image 1 Highlights: 27% of OMPs detected in RSF influents removed during filtration. Structure of ten transformation products from RSF effluents elucidated. Two novel transformation products identified using BioTransformer prediction. Microbial community similar in influent and effluent, different in filter medium. Overall OMP removal efficiencies not related to microbial community composition.